Spatial and temporal distribution of benthic foraminiferal faunas in the Bay Biscay - Jorissen, Frans J.; Fontanier, C.; Duchemin, G.; Hess, S.; Langenzaal, S.; Griveaud, C.; Barras, C.; Hohenegger, J.; Anschutz, P. (Anuário do Instituto de Geociências, 2006)
Abstract